Kendala Bank Syariah dalam Mendukung Pengembangan UMKM Pasca Lahirnya Qanun LKS 11 Tahun 2018 - Isnaliana, Isnaliana; Rifa Ul Khairi Fachruddin (Jihbiz: Global Journal of Islamic Banking and Finance, 2026)
The implementation of the Islamic Financial Institutions (LKS) Qanun Number 11 of 2018 in Aceh positions Islamic banks as strategic actors in supporting the development of Micro, Small, and Medium Enterprises (MSMEs). However, the implementation of this regulation has not yet fully and optimally impacted the strengthening of MSMEs, particularly in Banda Aceh City. This study aims to analyze in depth the obstacles faced by Bank Aceh Syariah and Bank Syariah Indonesia in supporting MSME development following the issuance of the LKS Qanun. The methodology used was a descriptive qualitative approach with field research. Data were collected through semi-structured interviews with bank representatives, and documentation studies, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results of the study indicate that although MSME financing has increased, Islamic banks still face various obstacles, particularly in the aspects of human resource development and marketing. These obstacles include the lack of an integrated MSME Center, weak mapping and clustering of MSMEs, limited business mentoring, minimal cross-institutional collaboration, and limited MSME involvement in promotional events. These findings indicate that the role of Islamic banks is still predominantly in financial intermediation, not fully implementing its MSME empowerment function comprehensively. Therefore, strengthening institutional and collaborative strategies is key to optimizing the implementation of the Qanun LKS and promoting MSMEs as a main pillar of the Acehnese economy.